2018
DOI: 10.1039/c8cc05428b
|View full text |Cite
|
Sign up to set email alerts
|

MOF/polymer composite synthesized using a double solvent method offers enhanced water and CO2 adsorption properties

Abstract: A double solvent method is for the first time used to synthesize a polymer composite that is constructed by a Ni-pyrazolate MOF and polydopamine (PDA). The resulting composite shows significantly enhanced water and CO adsorption properties compared to the parent MOF and the composite synthesized without the double solvent method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…The latter is likely due to new interactions between the CO 2 and the nitrogen species found in PDA and strongly polarizing C-F species in the per-uoro coating. 60,61 To test the improved stability of ZIF-67@PDA-SF (contact angle: 147 ), the parent MOF and composite were soaked in an aqueous H 2 SO 4 (pH ¼ 3) and NaOH solution (pH ¼ 13). While the parent structure completely degrades in either solution, as indicated by the XRD pattern and SEM images ( Fig.…”
Section: Extension Of the Current Strategy In Other Mofsmentioning
confidence: 99%
“…The latter is likely due to new interactions between the CO 2 and the nitrogen species found in PDA and strongly polarizing C-F species in the per-uoro coating. 60,61 To test the improved stability of ZIF-67@PDA-SF (contact angle: 147 ), the parent MOF and composite were soaked in an aqueous H 2 SO 4 (pH ¼ 3) and NaOH solution (pH ¼ 13). While the parent structure completely degrades in either solution, as indicated by the XRD pattern and SEM images ( Fig.…”
Section: Extension Of the Current Strategy In Other Mofsmentioning
confidence: 99%
“…This observation is likely due to the presence of amine groups on the polydopamine backbone combined with increased accessible surface area. 51 TGA analysis of the Ni 2 (NDISA)-PDA in air revealed that the polymer loading is $20.5 wt% (Fig. S10 †).…”
Section: Resultsmentioning
confidence: 99%
“…A large number of MOF‐polymer composites have been also reported in the past years, giving rise to materials with improved CO 2 adsorption capacity. Nitrogen rich polymers such as polydopamine, polyethyleneimine, polyether‐block‐amide have been used in combination with Ni‐pyrazolate, MIL‐101 and MOF‐808 …”
Section: Introductionmentioning
confidence: 99%